PENINGKATAN PRODUKSI JAMUR TIRAM DENGAN APLIKASI TEKNOLOGI TEPAT GUNA - Atmika, I.K.A.; Suriadi, I.G.A.K.; Budiana, I.M.D.; Arda, I.G. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
UD Ayu Dewata Jamur is an oyster mushroom cultivation business located in the Tegehe banjar of BatubulanGianyar village. Oyster mushroom production is simply packaged in a 1 kg plastic bag. This business has problems related to efficiency and productivity caused by unsuitable temperature and humidity of the incubation chamber for messelium. The manager of oyster mushroom cultivation does not have enough skills yet and educational background are still low. The aim and outcome of this activity is to produce a mechanized process of regulating the temperature and humidity of the messelium growth chamber, which is equipped with semi-automatic water or mist spraying. Besides that the team also provided knowledge about management, work safety and product quality control in relation to the application of this mechanization. The method that offered in this program is to design and install a semi-automatic spray mechanization that is also equipped with an indicator of temperature and humidity. Activities in the partners was carried on August 25, 2019, August 30, 2019, and September 2, 2019 at the UD Ayu Dewata Jamur oyster mushroom cultivation in Batubulan village, Sukawati district, Gianyar, Bali. The initial activity begins with cleaning and preparing the installation place for mechanized spray installation of water or mist. Next is the installation and testing of a water or mist spraying system. Monitoring activities carried out on October 2, 2019, and obtained by oyster mushrooms growing very well. Keywords : messelium, oyster mushroom, mechanization, temperature indicator, semi automatic